AB0463 A review of the outcomes of women with rheumatoid arthritis (RA) treated with biologic agents attending the sheffield combined obstetrics and rheumatology clinic 2002 to 2013. (12th June 2018) - Smith, R.; Kilding, R.; Kuet, K.-P.; Fairlie, F.; Jokhi, R.; Bonnett, T.; Smith, M.; Akil, M.
Abstract : Background: Women with RA have increased risk of complications including preeclampsia, low birth weight babies and Caesarean sections compared with unaffected women. 1 Higher levels of disease activity have a negative influence on birth weight. 2 More women are being treated with biologic agents, and there is growing evidence for their safe use in pregnancy. 3 Objectives: To assess disease activity during pregnancy, and to review foetal and maternal outcomes. Methods: Retrospective review of case notes. Results: Between 2002 and 2013, 17 women with RA treated with biologic agents attended the combined clinic. 13 were treated with Etanercept, 2 Adalimumab, 1 Tocilizumab and 1 Rituximab. 13 were in combination with disease modifying anti-rheumatic agents (DMARDs). There were 17 pregnancies. 2 women stopped their biologic prior to conception; 14 stopped on confirmation of pregnancy. 12 women had active disease during pregnancy. All had some form of steroid treatment, 3 had a DMARD introduced, and 1 restarted Etanercept at 20 weeks. There were 14 live births and 2 first trimester miscarriages. There was 1 elective Caesarean section, 7 spontaneous deliveries, and 5 inductions, 3 of which proceeded to Caesarean. Data is missing for 2 women. 10 babies were born at term, 3 were pre-term and data is missing for 2. 2 babies weighed less than 2500 g and 2 more than 4500 g. Data is missing for 3 babies. The low birth weight babies were also pre-term, had cardiac abnormalities and required admission to the neonatal unit. Both mothers had stopped Etanercept at confirmation of pregnancy. Both flared during pregnancy. 6 women developed complications: hypertension, diabetes, proteinuria, cervical incompetence, and hypothyroidism. 4 of these had active disease during their pregnancies. 2 babies had intrauterine growth restriction, 2 cardiac abnormalities and 1 macrosomia. All had mothers who flared during pregnancy. Conclusions: Our group of patients is small, but the outcomes are comparable to those of women with RA. There is no discernible increase in adverse events due to biologic use. In 2014 product recommendations were to stop biologics prior to conception. 4 Since 2016 the British Society for Rheumatology has advised that Etanercept and Adalimumab are compatible with use in the first and second trimesters. Tocilizumab and Rituximab should still be stopped prior to conception. 3 Local practice has changed to reflect this guidance, and the next step in this project is to review the data from more recent pregnancies to determine whether more prolonged use of biologics improves disease control and in turn foetal and maternal outcomes. References: [1] Lin H, et al. Increased risk of adverse pregnancy outcomes in women with rheumatoid arthritis. Annals of the Rheumatic Diseases2010;69(4):715–7. [2] de Man Y, et al. Association of higher rheumatoid arthritis disease activity during pregnancy with lower birth weight. Arthritis & Rheumatism60:3196–3206. [3] Flint J, et al. BSR and BHPR guideline on prescribing drugs in pregnancy and breastfeeding—Part I. Rheumatology. 2016;55(9):1693–1697. [4] Hyrich K, et al. Biologic therapies and pregnancy: the story so far. Rheumatology2014;53(8):1377–1385. Disclosure of Interest: None declared